Postpartum Secondary PPH Leading to Diagnosis of Choriocarcinoma: A Case Report - Maqsood, Zainab; Farkhanda, Tallat; Ejaz, Sara; Kousar, Tayyaba; Malik, Sobia Nawaz; Bilqis, Humaira (Journal of Rawalpindi Medical College, 2026)
Summary: One uncommon but extremely aggressive kind of gestational trophoblastic neoplasia (GTN) is postpartum choriocarcinoma. Its clinical manifestation frequently resembles typical subsequent postpartum hemorrhage sources, which could impede identification and raise maternal morbidity. Case Presentation: A woman with a history of three prior cesarean sections appeared with recurring severe vaginal bleeding. Twelve days after an emergency cesarean delivery, Conservative management was started after an initial examination revealed retained products of conception. However, hypovolemic shock caused the patient’s condition to worsen. Suspicion of GTN was raised by significantly high levels of β-human chorionic gonadotropin (β- hCG) in the serum and pelvic magnetic resonance imaging. An urgent surgical procedure was carried out since the bleeding was potentially fatal. Keywords: Postpartum Hemorrhage, beta-Human Chorionic Gonadotropin, Cesarean Section, Choriocarcinoma, Gestational Trophoblastic Neoplasia